Y Nendyrau - Dolma, Seran (Gwasg Pantycelyn, 2023)
Intro – Tudalen deitl – Hawlfraint – Cyflwyniad – Diolchiadau – Y Nendyrau – 1 – 2 – Aqualung I – 3 – 4 – 5 – 6 – 7 – Aqualung II – 8 – 9 – 10 – 11 – 12 – 13 – Aqualung III – 14 – 15 – 16 – 17 – 18 – 19 – 20 – 21 – Aqualung IV – 22 – 23 – Aqualung V – 24 – 25 – 26 – 27 – 28 – Aqualung VI – 29 – 30 – 31 – Aqualung VII – 32 – Aqualung VIII.
Description based on publisher supplied metadata and other sources